Development and validation of a simplified nomogram predicting individual critical illness of risk in COVID‐19: A retrospective study. Issue 4 (14th October 2020) - Xu, Ranran; Cui, Junwei; Hu, Liu; Wang, Yiru; Wang, Tao; Ye, Dawei; Lv, Yongman; Liu, Qingquan
Abstract: This study aims to screen useful predictors of critical cases among coronavirus disease 2019 (COVID‐19) patients and to develop a simple‐to‐use nomogram for clinical utility. A retrospective study was conducted that consisted of a primary cohort with 315 COVID‐19 patients and two validation cohorts with 69 and 123 patients, respectively. Logistic regression analyses were used to identify the independent risks of progression to critical. An individualized prediction model was developed, and calibration, decision curve, and clinical impact curves were used to assess the performance of the model. External validations for the predictive nomogram were also provided. The variables of age, comorbid diseases, neutrophil‐to‐lymphocyte ratio, d ‐dimer, C‐reactive protein, and platelet count were estimated to be independent predictors of progression to critical, which were incorporated to establish a model of the nomogram. It demonstrated good discrimination (with a C‐index of 0.923) and calibration. Good discrimination (C‐index, 0.882 and 0.906) and calibration were also noted on applying the nomogram in two validation cohorts. The clinical relevance of the nomogram was justified by the decision curve and clinical impact curve analysis. This study presents an individualized prediction nomogram incorporating six clinical characteristics, which can be conveniently applied to assess an individual's risk of progressing to critical COVID‐19. Highlights: Higher levels of NLR, D‐Dimer, CRP, and lower levels of platelet counts on admission were correlated with high odds ratio of critical COVID‐19. Developed a nomogram, which incorporates age, comorbidity diseases, NLR, D‐Dimer, CRP, and platelet count, provides an easy‐to‐use tool for clinicians to assess an individual's risk of progressing to critical with COVID‐19. According to the nomogram, timely make decisions or risk stratification management for critical cases in advance can successfully reduce the mortality rate of COVID‐19 patients.